2006
DOI: 10.13031/2013.22242
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Instrumental and Manual Inspection of Clingstone Peaches

Abstract: The flesh color and firmness of 13,140 clingstone peaches were measured instrumentally at the cannery receiving stations and compared with the current official subjective inspection methods of the California Department of Food and Agriculture. The instruments evaluated were a nondestructive impact firmness sensor, a traditional destructive penetrometer firmness sensor, and a tristimulus color sensor. Instrumental measurements for flesh color and nondestructive firmness gave good agreement (83% across all culti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
(10 reference statements)
1
11
0
Order By: Relevance
“…Flesh texture was scored in the orchard by trained personnel on fruit harvested at commercial ripening (onset of the veraison stage), as identified in each Assessment of the latter parameter by human inspectors' grading is coherent with instrumented measurements [26], and represents a non-destructive method capable to yield information on the time course of fruit texture evolution.…”
Section: Fruit Flesh Texture Phenotype Scoringmentioning
confidence: 99%
“…Flesh texture was scored in the orchard by trained personnel on fruit harvested at commercial ripening (onset of the veraison stage), as identified in each Assessment of the latter parameter by human inspectors' grading is coherent with instrumented measurements [26], and represents a non-destructive method capable to yield information on the time course of fruit texture evolution.…”
Section: Fruit Flesh Texture Phenotype Scoringmentioning
confidence: 99%
“…Automated devices have now become much more of a practical reality in many fields. For example, in a comparison of instrumented measurements of the flesh color and firmness of clingstone peaches with current subjective inspection methods, designed to sort the fruit into immature/mature and soft/firm categories, there was 83% agreement between the machine and human results (Slaughter, Crisosto, Hasey, & Thompson, 2006). The authors concluded that objective instrumental inspection methods hold promise as a replacement for current subjective methods.…”
Section: Automation and Inspectionmentioning
confidence: 99%
“…However, being on a scale from green to red, a* does not take into consideration the yellow colour component—mostly given by carotenoids—that is instead part of H°. Therefore, flesh H° has also been linked to maturity in yellow peach [ 30 ] and apricot [ 31 ]. In mature yellow peaches, flesh tends to be more orange or red than immature fruit, with a difference of approximately 5°H [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, flesh H° has also been linked to maturity in yellow peach [ 30 ] and apricot [ 31 ]. In mature yellow peaches, flesh tends to be more orange or red than immature fruit, with a difference of approximately 5°H [ 30 ]. Slaugther et al [ 30 ] also observed that flesh H° is a better indicator of maturity than flesh firmness in yellow clingstone peaches.…”
Section: Introductionmentioning
confidence: 99%